The contribution of several sub-watersheds within the Garang watershed in supplying the floods on 6 and 24 February 2021. Issue 1 (1st November 2022) - Pramono, I B; Basuki, T M; Priyanto, E; Yulianto, F; Fakhrudin, M; Imaduddin, F; Ramelan, A; Ibrahim, M H
Abstract: The flood incident of Garang watershed on 6 and 24 February 2021 inundated some of Semarang City. Total area of inundated area is about 47% of Semarang City or 176 km 2 . A research was conducted to estimate the contribution of sub-watersheds in flood peak and flood volume, and to analyze the causes of the flooding and its solutions. The flood peak discharge was estimated using Rational method and flood volume using Curve Number (CN) method. Geographic Information Syatem (GIS) is used for calculating Runoff coefficient and Curve Number. Overlay of landcover map, slope map, and soil map produce runoff coefficient map while the CN value was obtained from over lapping land cover maps, soil hydrology group, application of soil and water conservation techniques, hydrological conditions, and antecedent soil moisture content in each sub watershed. Garang watershed consists of 4 sub watersheds namely Garang upland, Kreyo, Kripik, and Garang lowland with area of 85.33; 65.36; 38.83; and 23.20 km 2 . The results showed that specific flood peak on 6 February 2021 were 3.9; 3.2; 3.6; and 3.4 m 3 /second/km 2 for the Garang upland, Kreyo, Kripik, and Garang low land subwatershed. Specific flood volume on Feb 6, 2021 were 91, 471; 91, 396; 96, 605; and 99, 058 m 3 /km 2 . Garang up land sub watershed has highest specific peak flow and Lower Garang sub watershed has highest specific flood volume. The cause of flooding in the Garang watershed was caused by high rainfall intensity and watershed degradation. Flood peak and flood volume can be reduced by applying some water conservation techniques and increasing vegetation cover.